Pendidikan Life Skill dan Kemandirian Santri Dalem Pondok Pesantren Haji Ya’qub Lirboyo Kediri - Mukhlison, Moch.; Arif, M Futukhul (Multidisciplinary Journal of Education , Economic and Culture, 2023)
Abstract: Today life skills education is very important for everyone, as well as students. They do not only seek religious knowledge, but must have the skills to build an independent Muslim. This research wants to know about life skills education owned by students at Haji Ya'qub Lirboyo Islamic boarding school Kediri. Vocational skills education, meaning skills related to vocational/skills that follow functional skills in the form of: cooking life skills, farming life skills, animal husbandry life skills, screen printing life skills, computer rental life skills, shop life skills, printing life skills, and trimming hair. This study also wanted to know the impact of life skills education on students at the Hajj Ya'qub Islamic Boarding School. The students will become professional individuals, honest individuals, creative individuals, responsible individuals, as well as diligent and tenacious individuals. This research is a qualitative research. With a total of 17 informants consisting of caregivers, administrators and students in this study conducted at the Haji Ya'qub Lirboyo Islamic Boarding School, Kediri, data collection used participant observation, in-depth interviews, and documentation. The results of the study show that the students in the Haji Ya'qub Lirboyo Islamic Boarding School, Kediri, have entrepreneurial individuals who are honest, creative and able to complete good and responsible tasks. The dalem students have several life skills which include the field of t-shirt screen printing, computer rental, cooking, agriculture, animal husbandry, barbershop, printing and shops.